Earthquake in Mexico: Mexico City governmentʼs health response - Armando Ahued-Ortega (Instituto Nacional de Salud Pública, 2018)
Before earthquake event of September 19, 2017, the Health Ministery of Mexico City and the institutions sectored to it, immediately implemented interventions: To receive patients with red and yellow priority, each unit in the hospital network of Sedesa, was prepared for massive reception of patients; scheduled surgeries were suspended, emergency patients were transferred to hospitalization or intensive therapy and those who could continue in their homes were discharged. With declaration of emergency, published by the head of government, the Ministery of Health, in coordination with other agencies of CDMX Government; federal institutions, parastatals, civil society organizations and private institu- tions, implemented the plans, protocols and actions defined exprofeso.